Remote Sensing and Nuclear Techniques for Soil Erosion Research in Forest Areas: Case Study of the Crveni Potok Catchment - Manić, Miloš; Đorđević, Milan; Đokić, Mrđan; Dragović, Ranko; Kićović, Dušan; Đorđević, Dejan; Jović, Mihajlo; Smičiklas, Ivana; Dragović, Snežana (Frontiers in Environmental Science, 2022)
Hilly terrains characterized by the looseness of the surface soil layer and the slope of the topographic surface are subjected to diverse erosion processes, which could greatly impact forest management. An erosive process was identified along the unstable slopes in most of the Crveni potok catchment in the southeastern part of Serbia. The results of this study indicate two erosion types of variable intensity, dominated by weak and moderate erosion, while severe erosion is identified at several locations. Water pressure in the pores of loose soil in the Crveni potok catchment generates gully erosion in parts of the catchment that are geologically predisposed by the composition of the parent substrate. The paper discusses the factors influencing gully erosion, such as soil density, the slope of the topographic surface, rainfall (precipitation amount, annual distribution), and vegetation characteristics. The set of used methodologies, including remote sensing, nuclear, and geospatial ones, provided an integrated assessment of factors affecting erosion in unstable forest areas. The soil erosion rates in the study area are estimated from inventories of fallout radionuclide 137Cs using conversion models. Airborne photogrammetry, terrestrial Structure-from-Motion (SfM) 360-degree camera photogrammetry, and Terrestrial Laser Scanning (TLS) are used to model complex geomorphological features of forest terrain. These techniques are found to be convenient for the quantification of the existing state of erosion (length, width, volume, and density of the gully systems) in the forest gullies. The remote sensing techniques provided an insight into the physiographic characteristics of the studied area important for determining its parts affected by erosion. The models obtained using different techniques are compared, techniques are evaluated, and their advantages and disadvantages are pointed out. This approach enables the identification of priority targets for soil conservation and site-specific remediation measures to foster sustainable forest management.